Learning-in-Practice: Student Teachers’ Voices Matter in Online Supervision Spaces - van Wyk, Micheal; Plaatjies, Bernadictus O. (Journal of Digital Learning and Education, 2025)
Learning in practice (LiP) involves teaching practice in authentic and simulated classroom environments for student teachers to grow professionally. This study explores the experiences and perspectives of student teachers of online supervision during their school-based teaching placements, focusing on the LiP, part of Work-Integrated Learning (WIL). This exploratory study adopted the qualitative approach within a single-case study design and utilised an online videoconferencing platform to interview twenty participants. The findings reveal how these placements serve as critical sites for professional growth, allowing student teachers to bridge theoretical knowledge with practical application. The findings revealed that supervisors provided constructive feedback and enhanced student teachers’ understanding of lesson planning, presentation and assessment. Further research could explore how virtual supervision, using platforms like MS Teams, influences the professional growth of student teachers.